Review on cost-value approach for requirements prioritization techniques - Tan, Amelia; Rozlina, Mohamed (IEEE, 2018)
The use of appropriate requirements prioritization techniques is crucial to the success of a software development project. There are many techniques offered with all the advantages and disadvantages of each. The question that come up frequently when doing requirements prioritization is “whether the priority list is generated based on customer's required value?” and “whether the value is generated comparable with the cost incurred for implementation?”. This paper aims to conduct an empirical systematic review to identify and review the requirements prioritization studies based on the cost-value approach. This literature review generates many insights including: reduction of pairwise comparisons, factors and aspects of cost-value, features that support cost value and cost-value constraints.